Cognitive associations with comprehensive gait and static balance measures in Parkinson's disease. (December 2019) - Morris, Rosie; Martini, Douglas N.; Smulders, Katrijn; Kelly, Valerie E.; Zabetian, Cyrus P.; Poston, Kathleen; Hiller, Amie; Chung, Kathryn A.; Yang, Laurice; Hu, Shu-Ching; Edwards, Karen L.; Cholerton, Brenna; et al.
Abstract: Introduction: Gait and balance impairments are cardinal features of Parkinson's disease (PD) that require cognitive input. However, the extent to which specific gait and balance characteristics relate to cognition in PD is unclear. In addition, independent models of gait and balance have not been developed from the same cohort. We aimed to i) develop models of gait and balance in a large PD cohort and ii) determine which gait and balance characteristics best related to cognition. Methods: One hundred and ninety-eight people with PD were recruited to the Pacific Udall Center. Using six inertial sensors (APDM, Inc.), comprehensive gait measurements were collected over a 2-min continuous walk and comprehensive static balance measures were collected during a 60-second standing task. Six domains of cognition were assessed: global cognition, attention, executive function, language, memory, and visuospatial function. Correlations and hierarchical linear regression determined independent associations. Results: Principal components analysis identified a gait model containing four domains accounting for 80.1% of total variance: pace/turning, rhythm, variability, and trunk. The balance model contained four independent domains accounting for 84.5% of total variance: sway area/jerkiness, sway velocity, sway frequency anteroposterior, and sway frequency mediolateral. Gait domains of pace/turning and variability were strongly associated with attention and executive function. Sway area and jerkiness of balance associated with attention and visuospatial function. Conclusions: Gait and balance characteristics were associated with specific types of cognition. The specific relationships between gait or balance with cognitive functions suggests shared cerebral cortical circuitry for mobility and cognitive functions. Highlights: Separate gait and balance models consisting of different domains were identified in PD. Pace and variability of gait were associated with attention and executive function. Measures of static balance were associated with attention and visuospatial function.